Analisa Alur Pendaftaran pada Pelayanan Pasien Rawat Jalan di Masa Pandemi Covid-19 Di Puskesmas Warnasari - Suryati, Diana; Ramadan, Abdi; Tahir, Mochamad (Lembaga Publikasi Ilmiah Nusantara, 2024)
Health center services have undergone significant changes to anticipate the potential increase in Covid-19 cases. In addition to virtual services, direct services to the community were also carried out in accordance with established health protocols. The Outpatient Registration Unit is a functional unit responsible for handling the registration of patients seeking outpatient care at the health center. One problem that emerged regarding the outpatient registration process was the community's lack of knowledge about the updated registration procedures introduced during the Covid-19 pandemic, which involved using a hotline or online consultation, followed by in-person medication pickup at the health center at a time specified by the doctor. The aim of this study is to identify the outpatient registration flow before, during, and the differences in the flow during the Covid-19 pandemic. This study employed a qualitative method in the form of descriptive research. Subjects in this study were selected using purposive sampling, with the main informants being the Head of the Health Center and the Head of Administration. Based on the findings, there were notable differences in the outpatient registration flow before and during the pandemic. Prior to the pandemic, patients registered and consulted directly at the health center. During the pandemic, the flow changed to using a hotline or online consultation system.